Aceitação parental: mães heterossexuais com filhos LGBTs - Costa, Moisés Carvalho (Universidade Federal de São Carlos, 2021)
The scientific production about the young LGBT population has highlighted aspects of vulnerability in this population, especially associating it with risk factors for risky sexual behavior, substance abuse, or the development of depressive and anxiety symptoms, and suicide ideation/attempts. On the other hand, there are studies that highlight the role of the family as an important protective factor for these same behaviors and factors, which can even mediate the association between identifying themselves as LGBT and exhibiting suicidal behavior. However, researches that addresses families of LGBT people are scarce and often highlight intra-family violence. This study, therefore, aimed to investigate and understand the process of parental acceptance of heterosexual parents who have children who identify themselves as LGBT people. For this, virtual interviews were carried out with mothers recruited through an invitation on social networks. The collected data were transcribed and analyzed using the Atlas.ti software. The results showed the importance of acceptance in alleviating the suffering of LGBT children and the relevance of sources of support in the acceptance process experienced by mothers. It is recommended that further studies be carried out addressing the issue in order to support interventions with families of LGBT people given the social relevance of the topic.
Parental acceptance: heterosexual mothers with LGBT children
Keywords: Aceitação parental; Pessoas LGBT; Família; Relações familiares; Parental acceptance; LGBT people; Family; Family relationships; Youth; Juventude; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL